Variability patterns of synchrotron and inverse Compton emission in blazars - Kirk, J. G.; Mastichiadis, A. (1999)
The acceleration of electrons at a shock front can produce characteristic patterns in the variation of the spectral index of the synchrotron emission as a function of flux. Using a simple model of the acceleration process, we present a discussion of these patterns and show how they compare with the variations in the emission of the same electrons via inverse Compton scattering of isotropically distributed target photons from an external source. The "soft lag" behaviour is observed in synchrotron emission, and should also be present in the inverse Compton flux. Shock models can also show "hard lag" behaviour of the synchrotron emission, but this is more difficult to achieve in the inverse Compton emission, because of Klein-Nishina effects. In some cases, the time scales of rise and fall of both the synchrotron and inverse Compton fluxes can depend on the acceleration mechanism.